Prevalence of PVL gene in some methicillin- resistant Staphylococcus sp. isolated from frozen, non frozen chickens and slaughtering workers in Kirkuk and Erbil - Shameran M. Tawfiq (Tikrit Journal of Pure Science)
The present study was performed on a total of 350 samples  (145 freshly chiken, 20 frozen chiken, 30 skin wounds of slaughtering workers,55 nasal swaps of workers and 100 swap from healthy skins of slaughtering warkers. The specimen taken from Shops selling live chickens (local) in Kirkuk and Erbil Governorates that inspected for Staphylococcus aureus. Fifty nine S. aureus isolates were isolated after clinical assessment for bacteriological examination. The isolates were distributed as 15(25%) from heathy workers skins, 5(8.5%) from workers wounds, 20(33.9) from freshly chickens samples,4(6.8%)from frozen chiken and 15 (25%) nasal swaps. The antibiotic susceptibility showed that the most effective antibiotics was Norfloxacin followed Ciprofloxacin, Gentamycin, and trimethoprim.20 isolates were choosen for PCR test out of 59 depending on sensitivity test (20 hsolate appeared resistance to methecillin disc), PCR results showed that mecA was detected in 12(20.3%) isolate. Distributed to 5(8.5%) fresh chiken, 3(5%) wound, 2(3.4%) healthy workers skins and 1 (1.7%) to each of nasal swabs of workers and frozen chickens of studied isolates.While pvl virulence gene was detected in 6(30%) isolates out of the 12 isolates were positive to mecA gene, 3(25%) fresh chickens, 2(16.7%) healthy workers skins, 1 (8.3%) in wound workers skins, None of the MRSA isolates from nasal workers swabs and frozen chickens were found positive for the PVL genes.The aim of this study to detect PVL gene among MRSA isolates.